2014
DOI: 10.1016/j.jaci.2013.12.1037
|View full text |Cite
|
Sign up to set email alerts
|

Peanut oral immunotherapy results in increased antigen-induced regulatory T-cell function and hypomethylation of forkhead box protein 3 (FOXP3)

Abstract: Background The mechanisms contributing to clinical immune tolerance remain incompletely understood. This study provides evidence for specific immune mechanisms that are associated with a model of operationally defined clinical tolerance. Objective Our overall objective was to study laboratory changes associated with clinical immune tolerance in antigen-induced T cells, basophils, and antibodies in subjects undergoing oral immunotherapy (OIT) for peanut allergy. Methods In a phase 1, single site study, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
427
5
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(453 citation statements)
references
References 84 publications
13
427
5
8
Order By: Relevance
“…tolerance (28,29) and in the mechanism of AIT efficacy (12,30,31). However, specific Treg-based immunotherapies have not been evaluated in the context of food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…tolerance (28,29) and in the mechanism of AIT efficacy (12,30,31). However, specific Treg-based immunotherapies have not been evaluated in the context of food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…After 6-12 months of OIT, there appears to be a shift away from T H 2 cytokine production towards a proinflammatory profile characterized by increased production of IL-1β and TNF-α [18]. Syed et al demonstrated increased function of antigen-specific CD4 + CD25 + FoxP3 + regulatory T cells following OIT, thus supporting the theory of active suppression of immune responses [56,58]. Gorelik et al [59] studied the mechanisms and duration of suppression of immune responses during peanut immunotherapy reported in the study by Narisety et al [60] and found that spontaneous and allergen-induced basophil reactivity, including IL-4 production, were suppressed during dose escalation and after 6 months of maintenance dosing.…”
Section: Immunologic Changes With Oitmentioning
confidence: 96%
“…[77][78][79][80] Can we devise tests to identify those subjects who are responding favorably to such OIT? In one small phase 1 single-site study, 4 of the 7 peanut allergic subjects who achieved sustained unresponsiveness to peanut (based on passing a DBPCFC at 3 months after discontinuation of OIT) had regained reactivity to peanut 3 months later, whereas the 3 other patients continued to exhibit a more persistent pattern of non-reactivity.…”
Section: Disease Monitoring In Allergic Disordersmentioning
confidence: 99%
“…In one small phase 1 single-site study, 4 of the 7 peanut allergic subjects who achieved sustained unresponsiveness to peanut (based on passing a DBPCFC at 3 months after discontinuation of OIT) had regained reactivity to peanut 3 months later, whereas the 3 other patients continued to exhibit a more persistent pattern of non-reactivity. 78 That study suggested that persistent demethylation of the FOXP3 gene in T regulatory cells (Tregs) may help to identify this "subtype" of patients who can maintain longer-term clinical non-reactivity to peanut even in the absence of regularly consuming maintenance doses of peanut. 78 Another study of a small number of subjects suggests that successful OIT in peanut allergic patients may be associated with the expansion of a population of allergen-specific CD4+ T cells that develop an 'anergic' T H 2 T cell phenotype, cells that were largely absent in both pretreatment participants and healthy controls.…”
Section: Disease Monitoring In Allergic Disordersmentioning
confidence: 99%
See 1 more Smart Citation